A participatory approach to Lesson Study in higher education. Issue 1 (4th January 2016) - Wood, Phil; Cajkler, Wasyl
Abstract : Purpose: – This Higher Education Academy funded study explored learning challenges faced by international students early in their post-graduate courses through the use of Participatory Lesson Study (PLS). The paper aims to discuss this issue. Design/methodology/approach: – Two approaches to PLS were explored. Students were interviewed after "research lesson seminars" about their learning experiences; before two seminars, groups of students participated in planning meetings to inform preparation of seminar content and activities. Findings: – Results suggest that PLS encourages a deep consideration of pedagogy by lecturers. Observation of student learning and post-seminar interviews highlighted the complex nature of the learning that unfolds during seminars. In some cases, student explanation of learning was dissonant with observations. Research limitations/implications: – This was a small-scale project which cannot offer generalised implications for practice. However, it should act as a starting point to develop PLS on a larger scale and in other pedagogic contexts. Practical implications: – This project led to reassessment of lecturers' pedagogic assumptions and to development of new approaches. Thematic analysis of pre- and post-seminar student responses highlighted several important issues: variation in approaches to participation in seminars, variable use of technologies to support learning, importance of differentiation for learning and task-types preferred by learners. Originality/value: – Results suggest that PLS facilitates the study of learning in higher education and the development of pedagogy, informed by and responsive to the needs of international students. As such, it has the potential to support any tutors working in higher education, whilst having wider, general utility to other groups approaching the development of pedagogy through Lesson Study.